Men times ten: does the presence of more men support inclusion of male educators in early childhood education and care?. Issue 1 (2nd January 2023) - Sullivan, Victoria; Coles, Laetitia; Xu, Yuwei; Thorpe, Karen
ABSTRACT: Retention rates for men in early childhood education and care (ECEC) are low. Exit is associated with experience of feeling 'other' perpetuated by judgements of men's sexuality, motives, and ability. In this paper, we take the unique circumstance of many men working together in ECEC to ask whether more men on staff improves experiences of inclusion. We analyse interviews with 10 men working in two Australian ECEC centres in which male educators comprise >20%, of the staff; ten times the international representation of men in the ECEC workforce. Our data identify a developmental process in which supports and mentorship, from female and male colleagues, are critical to retention early in career. Beyond, the building of a distinct male contribution underpins continuing career engagement. However, with the presence of more men new tensions emerge as the 'alien invader' becomes the face of the centre, potentially eclipsing the contribution of female colleagues.